The Application of the FMADM Electre Algorithm in Diagnosing the Level of Drug Addiction in Adolescents - Muchain, Alfira Nafhan; Zufria, Ilka; Fakhriza, M. (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
Drug abuse among adolescents was difficult to identify early without official examinations, while manual methods were often inaccurate. The process of determining rehabilitation also faced challenges due to the lack of technology-based support systems capable of effectively analyzing the level of addiction and type of drug used, resulting in rehabilitation that was often not well-targeted. To address this issue, the algorithm was utilized to diagnose drug addiction in adolescents by providing scores or rankings indicating addiction levels: scores of 1 and 2 represented mild addiction, 3 and 4 indicated moderate addiction, and 5 or higher represented severe addiction. The FMADM-ELECTRE algorithm recommended various types of rehabilitation actions for recovery. It offered precise evaluation ranges and scores, simplifying the classification and determination of appropriate detoxification measures for each type of drug-addicted adolescent. This system classified three levels of drug addiction among adolescents, corresponding to three stages of rehabilitation for drug addicts: non-medical (social) rehabilitation, medical rehabilitation (detoxification), and aftercare (post-rehabilitation). Additionally, the web-based support system was designed to be accessible across various devices, including laptops, computers, tablets, and smartphones, facilitating quicker and more efficient decision-making for relevant institutions. This approach also integrated multi-criteria methods to ensure fairness and accuracy in analysis, supporting a comprehensive rehabilitation process.